THE DYNAMICS OF IDENTITY CONSTRUCTION AMONG ETHNIC GROUPS IN BENUE STATE, NIGERIA (2014)
Since colonial times, identity construction and reconstruction has been a recurrent trend among ethnic groups in contemporary Benue State, Nigeria. Violent contestations have emerged from these reconstructions leading to loss of lives and properties. Understanding the dynamics of identity construction is critical to understanding the recurrence of violent contestations in Benue State. While a plethora of information exists on these contestations, there is dearth of data on the dynamics of identity construction in the State. This study, therefore examined how social thought and significant other-groups influence the dynamics of identity construction among the ethnic groups in Benue State. The research was anchored on Berger and Luckman’s constructionist theory. Descriptive and exploratory designs were adopted and respondents were purposely selected. Fifty In-Depth Interviews (IDIs) were held with gatekeepers among Tiv (10), Idoma (10), Igede (10), Etulo (10) and the Jukun (10) ethnic groups in their major traditional towns of Gboko, Otukpo, Oju, Adi respectively, to elicit information on social thought and significant other-group relations in identity construction. Ten Key Informant Interviews (2 per ethnic group) were conducted with individuals aged 60 years and above to provide information on identity construction in historical perspective. In addition, 20 Focus Group Discussions (FGDs) were held to elicit information on identity construction in contemporary times as well as the social relations of identity construction. Different FGDs were held for males and females ages 18-39 and < 40 years. Archival research and 5 case studies of individuals, who were 18 years old at the time of the 1950-60s Tiv protests, were used to examine identity construction in historical perspective. Data generated were subjected to content analyses. The Tiv and Idoma were the significant other-groups whose perceptions and attitudes influenced the reconstruction of identity of other ethnic groups of Etulo, Jukun and Igede. Their designation as significant-other groups was based on population, recognition by the State as the ‘majority’ and the creation of the Tiv and Idoma traditional rulership institution. The significant other-groups constructed their social thought identities based on their dominance and control of State resources while the other ethnic groups constructed their social thought as ‘enslaved’ and ‘dominated’ with a desire for change. The other ethnic groups of Etulo and Jukun reconstructed their identity as distinct from the Tiv. The Igede reconstructed their identity as distinct from the Idoma. Hence the Etulo, Jukun and Igede created social thought to emphasise and reify their distinctiveness. The Tiv and Idoma had a disparaging identity construction with regards to the ‘minorities’. Identity construction was spear-headed by charismatic individuals and groups who had a vision for the liberation of their ethnic groups. Spearheads with varying characteristics emerged as the need for new identities arose. Ethnic groups used identity construction to attract development from the State through facilitators and the creation of socio-cultural organisations to mobilise for community development. Government should ensure equitable distribution of resources and empower ‘minority groups’.